Major Microbiota Profile of Breast Cancer From Faecal Specimen and Cancerous Breast Tissue: A Comprehensive Systematic Review - Annisa, Annisa; Perdana Putri, Rachma Greta; Solikhah, Solikhah (Indonesian Journal of Cancer, 2023)
Background: The microbiota population in breast cancer tissue is known to have a crucial role in the tumor microenvironment supporting developmental ability. Despite a heterogeneous profile, the relationship between microbiota and breast cancer is still not fully understood. Therefore, this study aimed to explain the major microbiota profile associated with breast cancer and explore potential biological connections Methods: Following the PRISMA guidelines, the literature review investigated the diverse composition of microbiota profiles in breast cancer patients compared to those in normal conditions. Utilizing the PICO framework, a comprehensive search was conducted on the Pubmed and Google Scholar databases. The searches were restricted to open-access articles from the last 5 years. Additionally, critical appraisals are conducted for quality assessment. Results: A total of 145 articles were identified using the relevant keywords, out of which 17 successfully passed filtering and screening for inclusion in the review. Major microbiota observed in breast cancer patients included firmicutes, proteobacteria, actinobacteria, and bacteroidetes. The microbiota profile was influenced by factors such as cancer subtype, menopausal history, and tumor severity. These microorganisms play a role in the inflammatory response to their metabolite products and modulate hormonal changes, potentially enhancing tumor survival. Conclusions: Generalizing the expression of microbiota profile both in the gut or its tissue might be challenging due to its multifactorial nature, dependent on patient characteristics such as age, menopausal status, BMI, tumor grade, and subtype. The study suggests that the major microbiota that shows increased prevalence in breast cancer include firmicutes, proteobacteria, actinobacteria, bacteroidetes, and blautia, each playing a distinct role in the developmental process.